TINGKAT KEPUASAN DAN KEPATUHAN PETANI TEBU TERHADAP POLA KERJASAMA DENGAN PABRIK GULA GEMPOLKREP - Tjahaja Amir, Indra (MAPETA, 2010)
The purpose of this study is 1) to determine the level of satisfaction and adherence to the rights andobligations of farmers partnered, 2) to know the benefits and constraints of cooperation patterns, and 3) to analyze the revenue and efficiency of Partners and Non-Partners Sugarcane Farmers in various keprasan ways. The results showed that 1) the highest level of satisfaction of the rights of farmers in the pattern of cooperation is the ease of getting guidance, assurance system for profit sharing and satisfaction in getting the input, 2) the constraints faced by Gempolkrep Sugar Mill is an old machine, cutting transport activity has not met decent standard of minced (sweet, clean and fresh), and 3) obtained the highest income of farmers is keprasan first partners, while non-partners are third keprasan. The highest income earned partners are the first keprasan, while non-partners are third keprasan.Keywords: Pattern of partnership, the level of satisfaction and adherence